Objectives of Sharia in Spreading Peace and Rejecting Extremism and its Impact on Societal Peace (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2015)
The research problem is summed up in the reality in which we live, as it is full of the phenomena of extremism and extremism, and it is not hidden from everyone what Muslims have gone through in recent years because of that, and what is more dangerous than that is the attribution of these matters to the true Islamic religion and Islam is innocent of that.  All that we have seen and see of these negative manifestations and others is caused by ignorance of the blessed Sharia of Islam, which as soon as a person clings to it takes him by the hand to the gardens of advancement, prosperity, glory, peace and security, but the opposite occurs because of the abandonment of the teachings of Sharia or the wrong application of it. Therefore, the research aims to demonstrate the importance of the legal purposes in the life of the nation at all times, and to understand these purposes that make the Muslim on a firm footing from the gifts of Islamic law calling for all beauty, perfection and goodness, and rejecting all corruption, bad and evil, and that one of the most important purposes of the noble law is to preserve the entity of this structure  The honorable Lord, and the maintenance of everything related to him, to achieve the desired honor from him to be active in life spiritually, intellectually and physically, spreading goodness and peace in all its meanings, and reconstructing the earth and making homelands.  The research plan consisted of three topics, in the first it showed the concept of legal purposes in its general framework, and in the second it explained the legal purposes in making peace and greetings, and the third was in explaining the legal purposes in rejecting extremism and hostility.  The research showed that one of the necessary purposes in our true religion is to make peace and spread security in its essence and all its means leading to it, as well as reject extremism, extremism, and hatred, and that activating these purposes creates a clean, safe, and dignified society that is happy with coexistence, growing, prospering, advancing and developing, and striving to consolidate these concepts and then  Its application is the way to survival and prosperity, and on the contrary, societies are to annihilation and decline, we seek refuge in God Almighty from that, and these concepts are not disputed by the scholars, as they are an activation of the noble and clear texts, and they are in accordance with the spirit of the true Islamic religion, and according to the principles of achieving the objectives, rulings are derived in a manner that achieves the main purpose of creation in  Realizing their succession on earth in an atmosphere of peace and security that should be achieved in all humanitarian fields.